CONSUMPTION OF CARBONATED BEVERAGES AND THE RISK FOR GASTROINTESTINAL DISEASE: A SYSTEMATIC REVIEW - Puspo Edi Giriwono; Nuri Andarwulan; Rimbawan Rimbawan; Deddy Muchtadi (Persagi, 2014)
ABSTRACTIssues of different effects of carbonated soft drinks to human health have been circulated and analyzed in both scientific and non-scientific approaches. However, there is few publications discussing the specific effect of carbonation on human health and, more often than not, studies have largely concentrated on the effect of sugar or calorie content in carbonated beverages in affecting our health. Thus the effect of carbonation itself on human health is then lost in arguments contradicting or reaffirming the effect of carbonated soft drinks. We conducted this systematic review to specifically observe current findings on the effect of carbonation in beverages on human health. This systematic review was conducted using Scirus search engine to list articles relevant with keywords such as CO2, carbonated beverage, carbonation, sparkling water, gastrointestinal, gastro-esophageal and adenocarcinoma. Next, articles were obtained from numerous databases and screened for their relevance and context. Finally, peer reading and discussion were conducted for the writing of this article. The results of this systematic review observed three major article subjects currently correlated with exclusive effect of carbonation on gastrointestinal health. Published studies indicate that oral cavity/dental health, gastro-esophageal reflux and most recently esophageal adenocarcinoma are discussed frequently and observed in population studies in different countries consuming significant quantities of carbonated beverages. Eight articles (40%) discussed dominant factors not correlated with carbonation which significantly affect dental erosions. Six (33%) articles observed no clear clinical significance carbonation promotes or exacerbate gastro-esophageal reflux. Interestingly, five (27%) articles reported insignificant correlation, even inversed, of carbonation on esophageal carcinoma.Currently available scientific studies on populations in multiple countries show that the effect of carbonation in beverages has non-significant (statistically) effect on the health of the gastrointestinal tract.Keywords: Carbonated beverages, gastrointestinal, GERD, esophageal adenocarcinoma*ABSTRAKIsu mengenai dampak karbonasi pada minuman ringan terhadap kesehatan, terutama kesehatan saluran pencernaan, telah banyak beredar beserta pembahasannya, baik secara ilmiah maupun tidak. Efek kesehatan dari unsur karbonasi pada minuman ringan sangat jarang dibahas dan dipublikasikan pada jurnal ilmiah. Melakukan systematic review status ilmiah terkini khusus mengenai dampak karbonasi dalam berbagai produk minuman terhadap kesehatan saluran pencernaan. Scirus search engine digunakan untuk melacak artikel ilmiah dengan kata kunci khusus, yakni CO2, carbonated beverage, carbonation, sparkling water, gastrointestinal, gastro-esophageal and adenocarcinoma. Tahap ini dilanjutkan dengan penapisan (screening) untuk kesesuaian subjek artikel dan akses. Tahap terakhir adalah focus group discussion bersama peer/ahli dalam bidang gizi, kesehatan dan keamanan pangan. Hasil dari systematic review memperlihatkan bahwa terdapat tiga kelompok pembahasan utama yang berhubungan dengan efek karbonasi terhadap kesehatan saluran pencernaan, yaitu kesehatan pada gigi/rongga mulut, refluks esofagus dan kanker esofagus. Hasil skrining menunjukkan 40 persen published articles membahas dental health, 33 persen membahas gastro-oestrophageal health dan 27 persen membahas esophageal adenocarcinoma. Delapan artikel yang membahas dental health menunjukkan erosi yang dapat terjadi disebabkan oleh faktor lain di luar karbonasi. Enam artikel yang membahas gastro-oestrophageal health menunjukkan tidak ada korelasi antara faktor karbonasi dengan refluks ataupun refluks kronis yang terjadi. Sementara 5 artikel memperlihatkan observasi yang berkorelasi terbalik dengan risiko munculnya kanker esofagus. Systematic review menunjukkan bahwa saat ini berbagai artikel ilmiah relevan yang sudah dipublikasikan menyimpulkan dampak karbonasi pada minuman terhadap kesehatan saluran pencernaan tidak signifikan secara statistik klinis. [Penel Gizi Makan 2014, 37(1): 69-76]Kata kunci: Minuman berkarbonasi, penyakit saluran pencernaan, GERD, esophageal adenocarcinoma